2023
DOI: 10.1007/s00383-023-05429-7
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of multi-modal pain management for same-day discharge after minimally invasive repair of pectus excavatum (Nuss procedure) in children

Abstract: Background Despite advancements in minimally invasive repair of pectus excavatum (MIRPE), Nuss procedure, postoperative pain control remains challenging. This report covers a multimodal regimen using bilateral single-shot paravertebral block (PVB) and bilateral thoracoscopic intercostal nerve (T3–T7) cryoablation, leading to significant reduction in length of stay (LOS) and high rate of same-day discharge. Methods This is a comparative study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…EPP only provides analgesia while in place whereas INC provides a prolonged analgesic effect; in the prior studies, EPPs were typically in place for 48–72 h postoperatively and were discontinued prior to discharge. When INC is used in combination with a multimodal pain regimen, the researchers found that patients were able to be routinely discharged on post operative day (POD) 1 ( 33 , 37 , 40 , 48 , 49 , 51 , 56 , 57 ). Recent publications have demonstrated the feasibility of a same-day discharge when INC is combined with a peripheral nerve block (PNB) with 65%–66% of patients being discharged on POD 0 ( 49 , 55 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EPP only provides analgesia while in place whereas INC provides a prolonged analgesic effect; in the prior studies, EPPs were typically in place for 48–72 h postoperatively and were discontinued prior to discharge. When INC is used in combination with a multimodal pain regimen, the researchers found that patients were able to be routinely discharged on post operative day (POD) 1 ( 33 , 37 , 40 , 48 , 49 , 51 , 56 , 57 ). Recent publications have demonstrated the feasibility of a same-day discharge when INC is combined with a peripheral nerve block (PNB) with 65%–66% of patients being discharged on POD 0 ( 49 , 55 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…When INC is used in combination with a multimodal pain regimen, the researchers found that patients were able to be routinely discharged on post operative day (POD) 1 ( 33 , 37 , 40 , 48 , 49 , 51 , 56 , 57 ). Recent publications have demonstrated the feasibility of a same-day discharge when INC is combined with a peripheral nerve block (PNB) with 65%–66% of patients being discharged on POD 0 ( 49 , 55 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective control of severe postoperative pain due to stretching of the intercostal nerves and chest wall is necessary to ensure early mobilization, adequate respiratory function, and overall patient satisfaction. 4…”
mentioning
confidence: 99%
“…3 Effective control of severe postoperative pain due to stretching of the intercostal nerves and chest wall is necessary to ensure early mobilization, adequate respiratory function, and overall patient satisfaction. 4 The most commonly used drugs for postoperative analgesia management are opioids, but these drugs have undesirable side effects such as nausea, vomiting, urinary retention, and ventilatory depression. 5 For this reason, clinicians are using regional anesthesia techniques for postoperative analgesia management.…”
mentioning
confidence: 99%